Are there any antenatal interventions that reduce trauma during vaginal delivery?. Issue 8 (August 2017) - Cavanagh, Christina; Sanchious, Alyson Lewis
Abstract : EVIDENCE‐BASED ANSWER : Antenatal perineal massage decreases risk of perineal trauma and episiotomies in primiparous but not multiparous women (SOR: A, meta‐analysis of RCTs). Using warm compresses and perineal massage during second stage of labor reduces the risk of third‐ and fourth‐degree perineal lacerations (SOR: A, metaanalysis of RCTs). Perineal injection of hyaluronidase at the onset of the second stage of labor does not appear to prevent perineal trauma (SOR: A, meta‐analysis of RCTs).